Tonsillectomy and its effect on ASO titre - Bharti, Prerana; Mohindroo, Shobha; Mohindroo, N. K.; Sharma, Devraj; Kanga, Anil (International Journal of Research in Medical Sciences, 2017)
Background: Acute tonsillitis is one of the most common manifestations of the upper respiratory tract infections. It is common in children and accounts for an incidence of about 32 per 1000 patients per year. The objective of this study was to determine the effect of tonsillectomy on ASO titre and to evaluate the sensitivity and specificity of throat swab culture. Methods: Present study performed a prospective study, a total number of 50 children were screened, out which 25 patients under the age of 15 years (16 male and 9 female), were included in the study, who were having chronic tonsillitis with raised anti-streptolysin O titre (>200IU/ml). All the patient underwent tonsillectomy and serological estimation of ASO titre was done at the end of first, second and third month post-surgery. Throat swab culture was performed prior to tonsillectomy and at the third month of follow up. Results: Twelve children (48%), twenty children (80%) and twenty-two children (88%) became serologically negative for ASO antibody at the end of first, second and third month respectively, with a statistically significant p value of 0.0001. The sensitivity and specificity of throat swab culture was 16% and 100% respectively. Conclusions: Tonsillectomy has a significant role in reducing the serological levels of anti-streptolysin O antibody and its reactivation, thereby decreasing the rate of complications associated with Group A-beta haemolytic streptococci.